The impact of the applied progressive muscle relaxation training on the levels of depression, anxiety, stress and health-related quality of life among prostate cancer patients / Mohamad Rodi Bin Isa - Isa, Mohamad Rodi (2014)
Introduction The main aim of this study was to determine the impact of the applied progressive muscle relaxation training (APMRT) on the levels of depression, anxiety, stress and general health-related quality of life (HRQOL) among prostate cancer patients. Methodology A quasi-experimental trial with repeated measurements conducted at two tertiary medical centres in Kuala Lumpur with a follow up period for six months. The intervention group comprised patients who were being followed up at University Malaya Medical Centre (UMMC) and the comparison group were patients who were followed up at Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Baseline information on socio-demographic characteristics, history of chronic diseases, lifestyles practices of the patients, current urinary complaints and cancer status and treatment for prostate cancer were collected via face to face interview and review of the medical records. The scores for depression, anxiety and stress were assessed by using Depression Anxiety Stress Scales (DASS) and the scoring for HRQOL was assessed by using Short Form Health Survey consisting 36 items (SF-36). The assessments were achieved through self-administered questionnaires. Results There were 109 patients from UMMC and 84 patients from UKMMC who were eligible for the study. In both groups, majority of them were: in the age group 70 to 80 years, Chinese, male were married, staying with their family members or partner and had secondary school education. The baseline socio-demographic characteristics, history of chronic diseases, lifestyle practices of the patients, current urinary complaints, current cancer status were comparable (p>0.05) in both groups except for the treatment for the prostate cancer. In comparison group, more patients (79.8%) were treated with zoladex injection (p<0.001) and in intervention group, more patients (42.2%) treated with lucrine injection (p<0.001). Hypertension was the highest co-morbidity besides prostate cancer (67.6%) and nocturia was the commonest urinary complaint among the patients (87.3%). Only 77 patients from UMMC and 78 patients from UKMMC eventually agreed to participate in the study. At the end of the study, there were 70 patients from UMMC and 68 patients from UKMMC who completed the study. The completion rates were 90.9% for intervention group and 88.2% for the comparison group. After implementation of the APMRT, it was observed that there were significant improvement for anxiety (p<0.001) and stress (p<0.001) but not for depression (p=0.784). APMRT also significantly increased in the score for mental component